(In)fertilidade do corpo e a trama psíquica - Curi, Paula Land (2012)
This thesis, developed from the perspective of Fundamental Psychopathology and psychoanalysis, aims to present some reflections on (in)fertility and spontaneous abortions, especially without determined causes, as a consequence of a clinical work with women who have experienced such phenomena. From the clinical situation, the development of this work led us built some directions to think of the metapsychology of portability/sustenance of a child. The text unfolds in six chapters. The first chapter is dedicated to consider the relations among clinical method, research on Fundamental Psychopathology and the paths that the author had gone through since her encounter with motherhood, and its clinic. The second chapter opens a dialogue between evolutionary biology and Fundamental Psychopathology, emphasizing human subject´s singularity and its mythical constructions. The third and fourth chapters seek to a bibliographic review of the phenomena treated, in other fields of knowledge, overcoming speeches that recur and do not effectively support explanations of these phenomena. The clinical case composes the fifth chapter of this work. Through it, we were led to raise some interrogations and reflect on the relation between (in)fertility manifested in body and life and the psychic plot of a psychopathological subject. In such a manner, we were encouraged to think and to highlight the tenuous relationships that are established in the field of procreation between nature and culture, especially on sixth chapter. For this, we turned to the myths and the evidences that are also present in an institution called maternity